AB0211 Expression of M2 Macrophages in the Skin of Systemic Sclerosis Patients with Active Capillaroscopic Pattern of Microangiopathy. (10th June 2014) - Soldano, S.; Villaggio, B.; Brizzolara, R.; Montagna, P.; Sulli, A.; Parodi, A.; Cutolo, M.
Abstract : Background: Recent evidences report the involvement of macrophages in the pathogenesis of systemic sclerosis (SSc) (1). Among macrophage populations, the alternatively activated macrophages (M2) are associated with T helper type 2 (Th2) responses and tissue repair, in which they increase fibrosis by expressing profibrotic molecules, such as TGFβ (2). M2 macrophages are characterized by high expression of several surface markers, primarily mannose receptor (CD206) and scavenger receptors (i.e. CD204) (3). Objectives: To detect the presence of M2 macrophages in the skin of SSc patients and to investigate the ability of SSc serum to activate cultured human monocytes into M2 macrophages. Methods: Skin biopsies were obtained from one-third of the distal forearm of 6 female SSc patients (mean age 64.8±6.9 years) and 3 age-matched healthy subjects during diagnostic procedures (Dermatological Clinic, University of Genova) and after signing informed consent. Nailfold videocapillaroscopy (NVC) was also performed to define the pattern of microangiopathy (4). In addiction, serum samples were obtained from SSc patients and healthy subjects. Human monocyte (THP1) cells were plated in Flex Perm chamber slides (1x10 6 cells/ml) and treated for 48 hrs with RPMI supplemented with 10% of serum from SSc patients and healthy subjects. The expressions of the macrophage marker CD68, as well as of two markers of M2 macrophage phenotype, CD204 (scavenger receptor A) and CD206, were investigated both on skin biopsies (by immunohistochemistry -IHC) and on cultured THP1 cells (by immunocytochemistry -ICC), using mouse anti-human primary antibodies. CD204 and CD206 protein synthesis was indicated as % of positive area. Results: In 4 "limited" SSc patients the NVC pattern was "early" (2 cases) and "active" (2 cases), whereas the "diffuse" SSc patients showed a "late" NVC pattern (2 cases). IHC on the skin of SSc patients showed the presence of macrophage infiltrate (CD68 + cells) except for the "late" NVC pattern, where no cells were detectable due to the excessive fibrosis. In particular, CD204 + and CD206 + cells (M2 macrophages) were better detectable in the skin of SSc patients with "active" NVC pattern (not in healthy subjects). The in vitro treatment with SSc serum (from these patients) induced the transition of THP1 monocytes into macrophages and the expression of CD204 and CD206. The expression of both M2 markers was higher after cell treatment with serum obtained from SSc patients with "active" NVC pattern compared to treatment with serum from healthy subjects (% of positive area: 5.03±1.02 vs.3.99±1.35 for CD204 and 4.11±0.93 vs. 2.79±1.02 for CD206). Conclusions: Preliminary observations confirm the presence of M2 macrophages in the SSc skin, in accordance with a recent study (1). M2 macrophages seem to be higher in the "active" NVC pattern compared to "early" NVC pattern and healthy subjects. Moreover, results suggest the presence of molecules (cytokines, growth factors such as TGFβ or endothelin-1) in serum of SSc patients with more active disease, potentially able to induce the M2 macrophage phenotype. References: Higashi-Kuwata N et al. Arthrit Res Ther 2010;12:R128. Wynn TA et al. Nat Med 2012;18:1028-40. Mantovani A et al. J Pathol 2013;229:176-85. Cutolo M et al. J Rheumatol 2010;37:1174-80 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3739